The organisation of the preventative and curative medical services and hospital and laboratory systems under a Ministry of Health (London : Co-operative Printing Society)
1919 1919 1910s 18 pages THE LABOUR PARTY. THE ORGANISATION OF THE PREVENTATIVE AND CURATIVE MEDICAL SERVICES AND HOSPITAL AND LABORATORY SYSTEMS UNDER A MINISTRY OF HEALTH. THE POSITION OF THE GENERAL MEDICAL PRACTITIONERS IN A REORGANISED SYSTEM OF PUBLIC HEALTH. THE MINISTRY OF HEALTH. MEMORANDA Prepared by the Advisory Committee on Public Health Price 6d.; by post, 7d. 33, ECCLESTON SQUARE, LONDON, S.W. 1. 36/H24/6